The Evaluation of The Project on Strengthening The Students' Pancasila Profile in SMKN 7 Surakarta - Pujihastuti, Asri; Waluyo, Teguh; Sumardi, S (Universitas Muhammadiyah Surakarta, 2023)
The implementation of kurikulum Merdeka presents a significant challenge, particularly in developing students' character aligned with the Pancasila Student Profile. To address this, SMKN 7 Surakarta introduced the Pancasila Student Profile Strengthening Project (P5) as part of Kurikulum Merdeka. This study focuses on evaluating the P5 implementation at SMKN 7 Surakarta, specifically its planning stage using the P5 module created by teachers. The research adopts the CIPP (Context, Input, Process, Product) method to assess the implementation. A qualitative approach was employed, analyzing survey data through questionnaires and providing descriptive explanations of the findings. The study concluded that: 1) teachers successfully developed a P5 module following module-making principles, applicable to class X students, 2) teachers enhanced the quality of teaching material modules, particularly those related to fieldwork practice, and 3) the P5 module effectively strengthened the implementation of the independent curriculum.